The effect of market orientation as mediator to strategic planning practices and performance relationship: Evidence from Malaysian SMEs - Idar, Raduwan; Yusoff, Yuslina; Mahmood, Rosli (Elsevier Ltd., 2012)
The aim of this research is to examine direct relationship bet ween strategic planning practices and market orient at ion and the mediating effect of market orient at ion (MO) on the relationship between strategic planning practices (SPP) and SMEs” performance in Malaysia.It proposed a quantitative analysis in which market orientation and strategic planning practices are key success factors of SMEs.Data were collect ed by means of a mail survey questionnaire completed by owner/managers randomly selected from a sampling frame of registered SMEs.The integrated questionnaire was used to measure the strategic planning practices of firms using thirty four items developed from several authors and market orientation was measured using a nine item scale adapted from Narver & Slater (1990).Firms” performance measurement was based on subjective evaluation involving self-report ed measures.The findings reveal that significant relationships exist between strategic planning practices and performance, and also between market orientation and performance.While market orientation was found to partially mediate the strategic planning practices and performance relationships.These findings may be of help to the owner/managers of SMEs to be more market oriented and practicing strategic planning in order for them to survive the intensely in competitive market environment.